Pembuatan Chatbot Telegram untuk Layanan Pencarian Al-Quran - Lawami, Reza Haya; Harahap, Nazruddin Safaat; Yusra; Iskandar, Iwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The use of information technology in everyday life has become commonplace in today's society and is increasingly expanding into various fields, including access to the Qur'an. Although many digital Qur'an applications are available, a more flexible and interactive feature is still needed. The research focuses on developing a Telegram chatbot to facilitate the search for the Qur'an. The waterfall approach is used in developing this chatbot system, including needs analysis, design, implementation, and testing. Data collected through observation was used to understand the weaknesses of the existing Al-Qur'an chatbot system and formulate the desired functional requirements of the bot. This chatbot allows users to search for Qur'anic verses based on surah, verse, keyword, and voice recording. User Acceptance Test (UAT) testing showed a high level of acceptance from users, with 88.57% of respondents strongly agreeing with the chatbot's functionality and performance. Thus, this Al-Qur'an search service Telegram chatbot successfully provides a new alternative to accessing and understanding the Al-Qur'an and helps Muslims and Al-Qur'an memorizers in the process of searching and understanding the verses more efficiently.